设int x[ ]={4,2,3,1},q,*p=&x[1];则执行语句q=(*--p)++后,变量q的值为( )。
A: 4
B: 3
C: 2
D: 1
A: 4
B: 3
C: 2
D: 1
举一反三
- 设int x[]={4,2,3,1},q,*p=&x[1];则执行语句q=(*--p)++后,变量q的值为( )。
- 设int x[]={4,2,3,1},q,*p=&x[1];则执行语句q=(*--p)++后,变量q的值为( )。
- 已知列表 x = [1, 2, 3, 4],那么执行语句 del x[1] 之后x的值为____________。 A: [2, 3, 4] B: [1, 3, 4] C: [] D: [1, 2, 3, 4]
- 已知x = ([1], [2]),那么执行语句x[0].append(3)后x的值为______。 A: ([1], [3], [2]) B: [1, [3], [2]] C: ([1, 3], [2]) D: [[1, 3], [2]]
- 定义int x[]={1,2,3,4};则x[1]的值是( )。 A: 2 B: 1 C: 3 D: 4